The precaution strategy toward the COVID-19 pandemic in the operating room of a tertiary hospital in Taiwan. Issue 2 (4th February 2021) - Hung, Jung-Jyh; Wang, Fu-Der; Ma, Hsu; Tsou, Mei-Yung; Dai, Hung-Da; Lin, Yi-Han; Chen, Wei-Ming; Liu, Chin-Su
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The pandemic of SARS-CoV-2 (COVID-19), which began in December 2019, spread mostly from person to person through respiratory droplets. A recommendation was issued to postpone all elective surgical practices. However, some confirmed or suspected COVID-19 patients required life-saving emergent surgeries. Methods: To facilitate emergent surgical interventions for these patients, we have reviewed the current literature and established an algorithm of precautions to be taken by operating room team members during the COVID-19 pandemic. Results: The initial algorithm of preparation for surgical intervention during the COVID-19 pandemic was relatively simple. However, the abrupt increase of confirmed COVID-19 cases due to returned overseas travelers since mid-March 2020 disrupted the routine hospital clinical service. Due to the large number of febrile patients, the algorithm was therefore revised according to travel history, occupation, contact and cluster history (TOCC), unexplained fever/symptoms, and emergent/nonemergent surgery. TOCC (+) patients presenting with otherwise unexplained fever/symptoms would be regarded as belonging to the fifth category of "severe special infectious pneumonia." If the patient requires emergent surgery to relieve the non-life-threatening disorders, two times of negative COVID-19 tests are necessary before the operation is approved. For life-threatening situations without two negative results of COVID-19 tests, the operation schedule should be approved by the Chairman of Surgery Management Committee. Conclusion: The application of a clear and integrated algorithm for operating room team members aids in effective personal protective equipment facilitation to keep both healthcare providers and patients safe as well as to prevent hospital-based transmission of COVID-19.